2018
DOI: 10.1007/s00296-018-4053-x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular system changes in rheumatoid arthritis patients with continued low disease activity

Abstract: Systemic inflammation and disease activity seem to contribute to excessive prevalence of cardiovascular (CV) diseases (CVDs) in patients with rheumatoid arthritis (RA). The objective of the study was to assess chosen CV parameters in RA patients who have continuous low disease activity. The study group consisted of 70 RA patients without known CVD and 33 healthy controls, of a comparable age. All RA patients had continued low disease activity (DAS28 ≤ 3.2) from 2 to 7 years. The groups were assessed for: blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 31 publications
0
19
0
2
Order By: Relevance
“…In our patients who had low disease activity (average DAS28‐ESR of 2.7), DAS28‐ESR correlated positively not with cIMT but with the development of plaques. A similar report concluded that in RA with continued low disease activity, the plaque score was more sensitive than the mean IMT in predicting the development of atherosclerosis or CVD . Other previous studies have reported that disease activity correlated positively with atherosclerosis or CVD .…”
Section: Discussionmentioning
confidence: 69%
“…In our patients who had low disease activity (average DAS28‐ESR of 2.7), DAS28‐ESR correlated positively not with cIMT but with the development of plaques. A similar report concluded that in RA with continued low disease activity, the plaque score was more sensitive than the mean IMT in predicting the development of atherosclerosis or CVD . Other previous studies have reported that disease activity correlated positively with atherosclerosis or CVD .…”
Section: Discussionmentioning
confidence: 69%
“…[21] зависимость концентрации NT-proBNP от степени активности РА повышает вероятность негативного воздействия воспа-О р и г и н а л ь н ы е и с с л е д о в а н и я лительных цитокинов на миокард. По данным других авторов, даже при низкой активности заболевания уровень NT-proBNP остается более высоким, чем у здоровых лиц [22]. Выявленная нами взаимосвязь концентрации NT-proBNP с возрастом согласуется с результатами других исследований пептида у больных РА [5,14,15,23] и в общей популяции [24,25].…”
Section: Discussionunclassified
“…The study was performed on outpatients with RA, treated in the Regional Outpatient Clinic in Rzeszów, Poland, as described previously [8]. All patients fulfilled the American College of Rheumatology (ACR)/European League Against Rheumatism (EULAR) classification criteria for RA [9].…”
Section: Methodsmentioning
confidence: 99%